The Vasohibin Family - Yasufumi Sato (MDPI AG, 2010)
Angiogenesis is regulated by the local balance between angiogenesis stimulators and inhibitors. A number of endogenous angiogenesis inhibitors have been found in the body. The origin of these inhibitors is mostly extrinsic to the vasculature. Recently, however, vascular endothelial cells themselves have been found to produce angiogenesis inhibitors including vasohibin-1. These intrinsic inhibitors are thought to regulate angiogenesis by an auto-regulatory or negative-feedback mechanism. This review will focus on vasohibin-1 produced by vascular endothelial cells and on its homologue, vasohibin-2.